PENGARUH SUKU BUNGA TERHADAP INFLASI DI INDONESIA PADA TAHUN 1994-2023 - Denisa Sri Wahyuni; Intan Pijar Azzahra; Meodina Syafitri; Muhammad Abdurrahman; Sindy Azizah Seviyanti; Dahri Tanjung (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the effect of interest rates on inflation in Indonesia over the past 20 years using simple linear regression methods. Data is obtained from secondary sources such as national journals, the Central Bureau of Statistics (BPS), and Bank Indonesia from 2004 to 2023. The results of statistical analysis show that interest rates have a strong relationship with inflation, with a correlation of 74.4%. The interest rate variable is able to explain 52.8% of the variation in the model regarding its effect on inflation. Simple regression analysis confirms that interest rates have a positive effect on inflation in Indonesia. In this context, every 1% increase in interest rates results in a 1.1% increase in inflation. Hypothesis testing results also show that the effect of interest rates on inflation is statistically significant. The implications of this study underscore the important role of interest rates in monetary policy to control inflation, as well as the need for an in-depth understanding of the economic factors that influence it. In conclusion, this study contributes significantly to the understanding of inflation dynamics in Indonesia, especially in the context of its relationship with interest rates. The results are expected to be an effective foundation for the development of better monetary policy in managing inflation in the future.